Accounting Conservatism and Company’s Profitability: The Moderating Effect of Ownership Concentration - Abu Nassar, Mohammad; Al Twerqi, Heba (Jordan Journal of Business Administration, 2021)
This study aims to investigate the effect of accounting conservatism on a company’s profitability and whether ownership concentration moderates the effect of accounting conservatism on a company’s profitability in Jordan. The study took a sample of 84 industrial and service companies listed in Amman Stock Exchange (ASE) between 2006 and 2016. Adopting a quantitative research design, a cross-sectional analysis is performed to test the hypotheses of the study. The study employs both an accrual-based approach and a market-to-book ratio (M/B) approach to examine the effect of accounting conservatism on a company’s profitability. Ownership concentration is measured by taking the percentage of common stocks maintained by shareholders who possess at least 5% of the total amount of a firm’s common shares. The companies’ profitability is measured by the return on equity (ROE). The results revealed that accrual-based conservatism has a significant negative effect on the company’s profitability. According to the M/B ratio approach of conservatism, firms with higher levels of accounting conservatism and M/B ratio appear to have better profitability. Additionally, the results disclosed that ownership concentration has no moderating impact on the effect of accounting conservatism on the company’s profitability. The study provides some recommendations for firms with a view to adopt different conservative practices which may enhance accounting information quality and the overall profitability.